Una nueva especie de Tepuihyla (Anura: HyUdae) del noroeste de Venezuela, con comentarios sobre su biogeografía - Mijares-Urrutia, Abraham; Manzanilla-Puppo, Jesús; La Marca, Enrique (Revista de Biología Tropical, 1999)
Anew species of treefrog, Tepuihyla celsae (Hylidae), is described based on 11 specimens from cloudforests (1250 m) of the Sierra de San Luis, state of Falcón, northwestem Venezuela. The new species is d1stinguished from its congeners by dorsal pattero dark-brown with sorne few, small and scattered white spots, upper Iip immaculate white, dorsum strongly tuberculated in both sexes, dorsal spicules absent, eye-naris distance longer than horizontal length of eye, fingers lacking webbing, axillary membrane absent. This new Tepuihyla extend the known range of the genus more !han 500 km northwesterward, and is the frrst report of the genus outside the Guyanan masif, adding new evidence to support a c10se biogeographic affinity among the Sierra de San Luís and the Cordillera de la Costa with .the highlands of the Guyanan región.